Comprehensive Assessment on the Environmental Conditions of Abandoned and Inactive Mines in the Philippines - Jessie Samaniego; Cris Reven Gibaga; Alexandria Tanciongco; Rasty Rastrullo; Norman Mendoza; Charles Darwin Racadio (ASEAN Journal on Science and Technology for Development, 2020)
Most abandoned and inactive mines in the Philippines pose high risks to human health and the environment due to the disturbed and exposed heavy metal-laden soils and sediments and water-filled open pit mines. Establishing these mines’ environmental conditions remains a challenge as it requires time, effort, resources, and faces a lack of funding as the economic phase of the mine has already ceased. In order to contribute to the solution on the assessment of abandoned and inactive mines, integrated methods with combined essential testing, sampling, and analyses of different environmental media present in the mine site are suggested in this paper. On-site and laboratory methods include analyses for water (surface water and groundwater characterization, quality assessment, and environmental isotope tracers), soils and sediments (heavy and trace metals, anomalous elements, erosion, and nutrient availability), air quality, and radiometric survey. These methods can be classified as rapid with complete data, and information can be gathered to support a health risk assessment in the area, as well as used as a guide for rehabilitation prioritization of the abandoned mines.